Sequência didática para o ensino de geografia: a aula de campo como estratégia metodológica - Silvano, Geanne Estevam (2022)
Geography is a science that studies the geographic space in order to understand the interactions between man and nature. By studying Geography it is possible to better understand the world we live in and understand how human actions directly interfere in society. Given this context, the present research was developed based on the following question: how to outline a didactic sequence for the teaching of Geography considering the Ilha de Santana Tourist Complex, in the city of Caicó - RN, as a space for teaching action? In this sense, it was defined as a general objective to produce a didactic sequence containing a methodological proposition under the scope of a field class, focused on the teaching of Geography in the 4th year of Basic Education, having as empirical reference the Santa Costa Tourist Complex - Ilha de Santana (Caicó/RN). Specifically, we sought to highlight the teaching of Geography as a school subject in the early years of Elementary School; recognize the place of Geography in the official documents that govern Brazilian education; identify the spatial objects that make up the field class and build the didactic-pedagogical design of the didactic sequence. As a justification, there is the fact that the teaching of Geography has been configured in a promising thematic field for carrying out scientific research that assumes different approaches, among which those that refer to methodological strategies allied to the production of didactic-pedagogical resources stand out. The research, in terms of objectives, constitutes an exploratory study of a descriptive nature, whose methodological procedures were bibliographic, documentary and field research. As for the treatment of the data and information obtained, it corresponds to a qualitative research. It is expected that the textual material (didactic sequence), now made available to Basic Education teachers, and interested in the subject, can contribute to the teaching action, especially with regard to field classes and the elaboration of didactic sequences in the area of Geography.